Inequality Experienced by Black Women Characters in Bernardine Evaristo’s Girl, Woman, Other: A Black Feminism Study - Wajiran, Wajiran; Labibah , Maulina (Journal of Language and Literature Studies, 2024)
Gender roles are determined by expectations and values within society, which can lead to stereotypes and prejudice. Stereotypes are judgments that are considered correct for a group, while racial stereotypes are assumptions about all people of the same race. These racial stereotypes can make life difficult for women. This research aims to analyze the inequality expressed in Girl, Woman, Other and how the disparity occurs in society. The study employs Kimberle Crenshaw's Black Feminism theory. Moreover, this study uses a qualitative descriptive research method to analyze the novel. The information, approach, and theories are drawn from books, dictionaries, internet sources, journals, encyclopedias, and other primary and secondary sources. The primary data is the novel Girl, Woman, Other. The result of this study is that the novel Girl, Woman, Other clearly illustrates that inequality occurs not only because there is one identity that is owned but because each character owns several intersecting social identities. Race, gender, class, and sexual orientation that intersect with one another are the leading causes of the inequalities experienced by the characters in Girl, Woman, Other. The inequality experienced by the six characters causes them to struggle to gain equality in society as human beings.